Professionalisierung pädagogischer Fach- und Lehrkräfte in der frühen MINT-Bildung - Kucharz, Diemut (Wissenschaftliche Untersuchungen zur Arbeit der Stiftung "Haus der kleinen Forscher", 2021)
The number of attended MINT training courses is of central importance for the development of professional competence in early MINT education. This is the conclusion reached in the thirteenth volume of the publication series of the "Haus der kleinen Forscher" (Little Scientists' House). It presents the results of two studies on the professional development of educational specialists and teachers in early MINT education.